"Allstarke so pa malo dlje ostale" - Zavratnik, Veronika (Etnolog. Nova vrsta (Ljubljana), 2016)
Material culture is an essential, inseparable part of culture and society, of individuals and groups. To understand the social world we need to understand its material components. In the light of the research of material culture the article addresses the different aspects of the (social) life of a chosen type of footwear - All Stars, defined as sports and leisure footwear. Synthesizing the stories on the chosen footwear and their owners reveals the outstanding segments of a two-way relationship that always emerges between the material environment and people. And this shows that shoes are part of who we are, and who we are becoming. They are the "framework" through which we face the world under our feet, and at the same time their materiality defines how we experience that world.
Keywords: materialna kultura; oblačilna kultura; obutev; Slovenci; Slovenes; identiteta; zgodovinski pregledi